Analysis of Lexical Spelling Errors in Basic Writing Production Among Second Semester Students at Universitas Negeri Medan - Yustina Sidabutar; Rabiah Adawi (Indonesian Journal of Advanced Research, 2023)
This research aims to analyze the types of French lexical spelling errors found in the writing of UNIMED students in basic writing production courses. The method used in this research is qualitative descriptive. The data collection technique uses student writing results during exams in basic writing production courses and Google forms. The results showed that there were 68 data on lexical spelling errors, 58 data (85.29%) on diacritical mark (accent) errors, 8 data (11.76%) on errors colored by non-functional errors and 2 data (2.95%) on segmentation faults. Based on the questionnaire filled out by the students, there are two factors responsible for these errors, namely interlingual factors and intralingual factors. Of these two factors, the main cause is intralingual factors. In addition, learners do not know the boundaries or rules of a language due to lack of knowledge about the material.